SerPUBLIC HEALTH SURVEILLANCE OF TRAVEL-ASSOCIATED LEGIONNAIRES’ DISEASE IN EUROPE AND MONTENEGRObian - Medenica, Sanja; Rakocevic, Bozidarka; Djordjevic, Zorica; Markovic, Darinka (HEALTH CARE, 2022)
The aim of this study is to show how public health surveillance of travel-associated Legionnaires’ disease was conducted in Europe, as well as in Montenegro. The estimations of the European Centre for Disease Prevention and Control (ECDC) indicate that every year about one thousand tourists from Europe get infected by legionellae during their holiday and stay at hotels across the continent. The European Legionnaires’ Disease Surveillance Network (ELDSNet) was established with the aim to detect, control and prevent cases, clusters and sources of outbreaks of travel-associated Legionnaires’ disease within the European Union (EU) and European Economic Area (EEA), and to assist with detection and response to outbreaks outside the EU/EEA. Sharing information leads to concrete and timely actions of member states of ELDSNet, so that residents of the EU/EEA who travel abroad are protected. ECDC recommends a set of measures that should be followed by public health authorities and tourist sector of the country which was visited by the traveler who caught this disease. If the measures are not carried out, information is published online and European tour operators can use the information when booking holiday packages abroad. Operating procedures provide a set of common measures which should be followed by all EU/EEA member states involved in the protection of their residents against Legionnaires’ disease. Each case of Legionnaires’ disease which is reported in tourists, who stayed in Montenegro, is epidemiologically analyzed according to the operating procedures of ELDS Network.
Keywords: Legionnaires’ disease, European Legionnaires’ Disease surveillance Network, travels